Cryopreserved platelet concentrate transfusions in 43 dogs: a retrospective study (2007–2013). Issue 5 (4th July 2016) - Ng, Zenithson Y.; Stokes, Jennifer E.; Alvarez, Lucia; Bartges, Joe W.
Abstract: Objective: To clinically characterize a group of thrombocytopenic dogs that received cryopreserved platelet concentrate (cPC) transfusion, assess efficacy of cPC treatment in improving patient outcome, and compare treated dogs to a control population of thrombocytopenic dogs that did not receive cPC transfusions. Design: Retrospective study. Setting: University teaching hospital. Animals: Eighty‐six client‐owned dogs (43 in treatment group, 43 in control group). Interventions: None. Measurements and Main Results: Medical records of thrombocytopenic dogs that received cPC transfusions and those of thrombocytopenic dogs that did not receive cPC (control population) from January 2007 through March 2013 were reviewed. Dogs receiving cPC were statistically more likely than controls to have a platelet trigger for cPC transfusion ( P = 0.01), lower platelet count ( P = 0.009) and hematocrit at presentation ( P = 0.001), and lower hematocrit after cPC ( P = 0.02). Although there was a statistically significant increase in platelet count from pre‐ to post‐cPC transfusion ( P = 0.002), cPC was not found to be effective in improving clinical bleeding or increasing survival compared to the control group. No other characteristics were statistically different between groups. No dogs receiving cPC had an acute transfusion reaction during hospitalization. Conclusions: In the population described in this study, cPC was not found to increase survival, but was well tolerated. Controlled, prospective studies are necessary to determine indications for and efficacy of cPC transfusions.